Nutritional aspects in chronic non-cancer pain: A systematic review - Xu Lou, Inmaculada; Gil-García, Eugenia; Cáceres-Matos, Rocío; Ali, Kamran; Molina, Esther (Frontiers in Nutrition, 2022)
Objectives: Chronic pain is an unpleasant emotional and sensory experience that can be accompanied by tissue damage that persists for more than three months. Recent studies show that certain nutritional strategies can help to improve pain, so this study aims to systematically review scientific evidence to understand and map the effect of the use of nutritional strategies on the presence or intensity of chronic non-cancer pain as well as the association of these nutritional aspects with the presence or intensity of chronic non-cancer pain. Study design: systematic review. Methods: Two independent researchers searched for randomized clinical trials and observational studies that explored the relationship between nutrition and chronic non-cancer pain in adults from 2010 to 2020 in PubMed, Web of Science, Scopus and Cochrane Library databases. A total of 24 studies were included, of which 20 were randomized clinical trials and 4 were observational studies. They are classified into the administration of nutritional supplements, dietary modification, and incorporation of food. Results: Of these studies, those that have a significant effect on pain are dietary modification and the use of nutritional supplements. On the other hand, the main results from the few observational studies included in this review point to the existence of an association relationship between less pain and a ketogenic or hypocaloric diet or adherence to the Mediterranean diet. Conclusions: Dietary modification seems to be one plausible therapeutic option to improve and relieve chronic non-cancer pain. However, more research is needed in this regard to obtain better conclusions.